PENINGKATAN SUN TRACKING OTOMATIS DAN AUTOFOCUS UNTUK SOLAR CELL ACTUATOR PADA PLTS - Tanjung, Dicky Ananda; Purba, Syamsul Bahri; Saputra, Angga Aditya; Aryza, Solly; Anisah, Siti (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The increasing population results in increased consumption of electrical energy, PLN as a government electricity provider company has an important role in distributing electrical energy from the power plant to consumers, but in reality PLN often performs power outages in certain areas. Therefore, an environmentally friendly electricity backup supply system was created by utilizing solar power as a source of electrical energy which is often known as PLTS, but PLTS which is commonly used has shortcomings in terms of generating electrical energy because the solar cell module cannot follow the direction of the light. sun. Electricity has been widely used by industry, offices, as well as for the general public and individuals. Increasing demand for electricity sources can be obtained from solar energy which is converted into electrical energy, by utilizing solar panels. Solar power can be used as an alternative electrical energy in the utilization of this solar power. Energy by using the photovoltaic process, which directly converts solar energy into electrical energy. Automatic solar tracking for solar power plants can be designed to meet the needs of large-scale households, which people can easily use Technology, This technology can be designed using some basic instruments. Like solar panels. LDR (Light Dependent Resistor), Arduino Microcontroller, AC Motor and Motor Driver.